Investigational PD-1 inhibitors in HL and NHL and biomarkers for predictors of response and outcome. (2nd January 2018) - Chang, Andres; Schlafer, Danielle; Flowers, Christopher R.; Allen, Pamela B.
ABSTRACT: Introduction : Inhibitors against the PD-1/PD-L1 pathway are revolutionizing the treatment and management of malignancies. Areas covered : We summarize our current understanding of the function of PD-1, its role in immune evasion, the clinical data available that support the use of PD-1 antagonist in Hodgkin and non-Hodgkin lymphomas, and potential predictors of response. Expert opinion : We anticipate that in the next 10 years, agents that modulate the immune system such as PD-1 antagonists will be increasingly used in favor over traditional cytotoxic chemotherapeutic agents. PD-1 antagonists will be combined with future immunotherapies or used as adjuncts to cellular therapy to boost tumor-specific immune responses.